Romanian agri-food trade with the new member states (nms-13) of the EU: A comparative analysis - Camelia Gavrilescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
After joining CEFTA in 1997, Romania established a relatively stable group of partner countries for its agri-food trade. Several factors contributed to the stability in time of this group, firstly the existence or establishment of preferential trade agreements, the geographical proximity, and last, but not least, the historical traditions. The exit from CEFTA and the accession to the EU of some of the partner countries, then of Romania itself, changed only temporarily the trade flows, until everyone's adaptation to the "new rules of the game". Among the new Member States of the EU (NMS-13), the main trading partners for Romania were and are Hungary, Bulgaria and Poland. The paper is analyzing the evolution of the agri-food trade flows with these countries, in terms of value and composition of the exchanges.
Keywords: 330; agri-food trade; CEFTA; NMS-13; Romania